Psychometric properties of telepressure measures in the workplace and private life among French-speaking employees - Raphaël Semaan; Liudmila Gamaiunova; Patricia Pereira Teixeira; Urs M. Nater; Raphaël Heinzer; José Haba-Rubio; Peter Vlerick; Ruben Cambier; Patrick Gomez (BMC Psychology)
Abstract Background Workplace telepressure and private life telepressure refer to the preoccupation with and the urge to respond quickly to electronic messages from people at work or in private life, respectively. We aimed to adapt and validate workplace and private life telepressure measures in French and to explore their nomological networks and relationships with psychological health and wellbeing. Methods Participants were recruited via flyers, local press, and social media to complete two online surveys. Participants had to be French-speaking employees working in Switzerland and regularly using information and communication technologies for work purposes. The sample included 347 employees (200 females, 146 males, one nonbinary individual; mean age: 36.8 years) who completed both surveys. The first questionnaire assessed sociodemographic characteristics and the workplace and private life telepressure measures. The second questionnaire, which was administered approximately two weeks later, assessed complementary sociodemographic characteristics, nomologicals (five technostress creators, workaholism, neuroticism, conscientiousness, and mindfulness), measures of psychological health and wellbeing (depression, anxiety, stress, and psychological detachment from work), and the two telepressure measures. Results Both telepressure measures exhibited strong psychometric properties, including validity, reliability, and measurement invariance across age, gender, and time. Confirmatory factor analysis revealed that the two-factor model (preoccupation and urge factors) provided a better fit than did the one-factor model for both measures. Correlation analyses revealed that both telepressure measures were significantly positively associated with techno-invasion, techno-complexity, techno-insecurity, workaholism, and neuroticism and negatively associated with mindfulness. However, only workplace telepressure was significantly associated with techno-overload, and neither telepressure measure was significantly associated with techno-uncertainty. Structural equation modeling showed that workplace telepressure significantly predicted stress, anxiety, depression, and psychological detachment from work, whereas private life telepressure significantly predicted stress, anxiety, and psychological detachment from work, but not depression. Most effects were significantly greater for workplace telepressure than for private life telepressure. Conclusions This study confirms the validity of the workplace telepressure and private life telepressure measures for use in French-speaking populations and contributes to our understanding of the role of these two constructs in employees' psychological health and wellbeing.